KADAR RESIDU ENROFLOKSASIN YANG DIBERIKAN PER ORAL DAN INTRAMUSKULER PADA IKAN NILA (Oreochromis niloticus) YANG DIINFEKSI Aeromonas salmonicida - , FERA ARYANTI, Prof. drh. Kurniasih, MV.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Use of enrofloxacin on livestock and aquaculture impact on the presence of residues in food and the formation of bacterial resistance to enrofloxacin in animals and humans. This study aims to determine the level of enrofloxacin residues which was given orally and intramuscularly in the tilapia (Oreochromis niloticus) meat infected by A. salmonicida at 1 week, 4 weeks and 8 weeks post medication. A total of 25 healthy tilapia fish are divided into 3 groups. Group 1 by 5 tails without treatment, while groups 2 and 3, each consisting of 10 fish were infected in 0.1 ml concentration 106 cells / ml of A. salmonicida subsp. smithia and A. salmonicida subsp. achromogenes given intramuscularly. Six days after infection, treatment with BaytrilÂ® is administered orally to group 2 and intramuscularly to group 3 for 5 days with therapeutic doses of 10 mg / kg bw. Week 1, week 4 and week 8 post-treatment for each group taken each 3 fish for enrofloksasin residue analysis by diffusion method on Mueller Hinton Agar (MHA) and quantitatively by using High Performance Liquid Chromatography (HPLC). Enrofloxacin residue examination with diffusion test at 1 week and 4 weeks post-treatment showed formation of inhibition zone, whereas at 8 weeks post-treatment showed no inhibition zone. In the quantitative test results, infected tilapia by A. salmonicida subsp. smithia and treated orally at 1 week, 4 weeks and 8 weeks post-treatment showed enrofloxacin residues an average of 33.0 Î¼g/g, 6.10 Î¼g/g and 0.0021 Î¼g/g, whereas residues in meat of infected tilapia by A. salmonicida subsp. achromogenes and enrofloxacin treated intramuscularly showed an average of 35.79 Î¼g/g, 2.18 Î¼g/g and 0.00065 Î¼g/g. Overall enrofloxacin residues found in tilapia meat after 1 week and 4 weeks post-treatment exceed the maximum residue limit according to the provisions of the National Standard of Indonesia at 0.01 Î¼g/g. Enrofloxacin treatment given orally produce higher average residue levels compare to intramuscularly administration, but not statistically significant effect on both residues found in tilapia meat both at 1 week and 4 weeks post-treatment.